Sitosterolemia: a review and update of pathophysiology, clinical spectrum, diagnosis, and management - Eun-Gyong Yoo (Annals of Pediatric Endocrinology & Metabolism, 2016)
Sitosterolemia is an autosomal recessive disorder characterized by increased plant sterol levels, xanthomas, and accelerated atherosclerosis. Although it was originally reported in patients with normolipemic xanthomas, severe hypercholesterolemia have been reported in patients with sitosterolemia, especially in children. Sitosterolemia is caused by increased intestinal absorption and decreased biliary excretion of sterols resulting from biallelic mutations in either ABCG5 or ABCG8, which encode the sterol efflux transporter ABCG5 and ABCG8. Patients with sitosterolemia show extreme phenotypic heterogeneity, ranging from almost asymptomatic individuals to those with severe hypercholesterolemia leading to accelerated atherosclerosis and premature cardiac death. Hematologic manifestations include hemolytic anemia with stomatocytosis, macrothrombocytopenia, splenomegaly, and abnormal bleeding. The mainstay of therapy includes dietary restriction of both cholesterol and plant sterols and the sterol absorption inhibitor, ezetimibe. Foods rich in plant sterols include vegetable oils, wheat germs, nuts, seeds, avocado, shortening, margarine and chocolate. Hypercholesterolemia in patients with sitosterolemia is dramatically responsive to low cholesterol diet and bile acid sequestrants. Plant sterol assay should be performed in patients with normocholesterolemic xanthomas, hypercholesterolemia with unexpectedly good response to dietary modifications or to cholesterol absorption inhibitors, or hypercholesterolemia with poor response to statins, or those with unexplained hemolytic anemia and macrothrombocytopenia. Because prognosis can be improved by proper management, it is important to find these patients out and diagnose correctly. This review article aimed to summarize recent publications on sitosterolemia, and to suggest clinical indications for plant sterol assay.